Anabolic steroids reduce spinal cord injury-related bone loss in rats associated with increased Wnt signaling. (1st November 2013) - Sun, Li; Pan, Jiangping; Peng, Yuanzhen; Wu, Yong; Li, Jianghua; Liu, Xuan; Qin, Yiwen; Bauman, William A.; Cardozo, Christopher; Zaidi, Mone; Qin, Weiping
<x xml:space="preserve">Abstract</x> Background Spinal cord injury (SCI) causes severe bone loss. At present, there is no practical treatment to delay or prevent bone loss in individuals with motor-complete SCI. Hypogonadism is common in men after SCI and may exacerbate bone loss. The anabolic steroid nandrolone reduces bone loss due to microgravity or nerve transection. Objective To determine whether nandrolone reduced bone loss after SCI and, if so, to explore the mechanisms of nandrolone action. Methods Male rats with complete transection of the spinal cord were administered nandrolone combined with a physiological replacement dose of testosterone, or vehicle, beginning on day 29 after SCI and continued for 28 days. Results SCI reduced distal femoral and proximal tibial bone mineral density (BMD) by 25 and 16%, respectively, at 56 days. This bone loss was attenuated by nandrolone. In ex vivo osteoclasts cultures, SCI increased mRNA levels for tartrate-resistant acid phosphatase (TRAP) and calcitonin receptor; nandrolone-normalized expression levels of these transcripts. In ex vivo osteoblast cultures, SCI increased receptor activator of NF-kB ligand (RANKL) mRNA levels but did not alter osteoprotegerin (OPG) mRNA expression; nandrolone-increased expression of OPG and OPG/RANKL ratio. SCI reduced mRNA levels of Wnt signaling-related genes Wnt3a, low-density lipoprotein receptor-related protein 5 (LRP5), Fzd5, Tcf7, and ectodermal-neural cortex 1 (ENC1) in osteoblasts, whereas nandrolone increased expression of each of these genes. Conclusions The results demonstrate that nandrolone reduces bone loss after SCI. A potential mechanism is suggested by our findings wherein nandrolone modulates genes for differentiation and activity of osteoclasts and osteoblasts, at least in part, through the activation of Wnt signaling.